Menilai Kesulitan Belajar Peserta Didik akibat Speech Disorder - Zurqoni, Zurqoni (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Speech disorder is one of the factors that causes learning difficulties of students because this disturbance will impede the communication and familiarization process in their learning community. Speech disorder not only causes disharmony in themselves but also brings negative influence in their learning activities, which in the long run will cause certain difficulties in achieving satisfactory academic performance. Speech disorder in commonly marked by some subtitution symtoms, distortion, omission, clonic spasm dan tonic spasm, which are caused by heredity or inappropriate treatment by people living surrounding the students. Currative effort can be done integratively both psychis therapy and physical medication in order to improve students harmonization as a prerequisite for learning activities.